PENGETAHUAN DAN PEMAHAMANPOLA ASUH ORANG TUATERHADAP ANAK DALAM KELUARGASEBAGAI SALAH SATU CARA MENCEGAH ANAK MEMILIKI KPERIBADIAN NEGATIF - Tuasikal M. Amin (Asian Journal of Innovation and Entrepreneurship, 2014)
Family environment is thenearest environment for children, so the family is also asource for the emergence of various nature in children. One factor that is thought to bebecause the incidence of negative behavior is the tendency of certain parenting fromtheir parents. Pattern foster parent is an interaction between parents and childrenduring the conduct of care, and every parenting contributes to the child's behavior.Contribution given can be negative or positive. Therefore, for each type of parenting arethe weaknesses and the strengths. In this regard, the parents should be more aware ofthe position and apply the parenting that most have little or no potential to buildstimulate negative behaviors in children's care. It is recognized that almost no parentswho practice parenting purely on one type. Trends in certain types of parenting seem tobe more widely used by parents. Or even parents parentingpractice is eclectic, to childcare means doing situationally.